Relationship Between Work Stress Level and Mental Workload to the Performance of Special School (SLB) Teachers Prof. Dr. Sri Soedewi Masjchun Sofwan, S.H. in Jambi City - Salsabila, Atika Putri; Rini, Willia Novita Eka; Rd. Halim (MultiTech Publisher, 2024)
The success of teachers in carrying out their duties is measured through performance. The higher the performance given, it means that the teacher is successful during the teaching process. This study aims to determine the relationship between work stress levels and mental workload with teacher performance. Cross-sectional design. The study was conducted at SLB Prof. Dr. Sri Soedewi Masjchun Sofwan, S.H. Jambi City from November to July 2024. The sampling technique was through Total Sampling with a sample size of 63 teachers. The questionnaires used were DASS-42 (work stress), Nasa-TLX (mental workload) and teacher performance questionnaires. Data analysis using the chi-square test (SPSS version 23). Based on the results of the study, it showed that 42.9% of teachers experienced moderate stress, 54.0% of teachers had high mental workload and the average teacher had good performance of 34.9%. The results of the bivariate analysis showed that the variable of work stress level with the category of experiencing stress was 24 (75.0) values (p = 0.000) PR value (4.650, 95% CI: 2.033 - 10.635), mental workload with a heavy category was 24 (70.6%) values (p = 0.000) PR value (4.094, 95% CI: 1.792 - 9.355). There is a relationship between the level of work stress and mental workload with teacher performance